2015
DOI: 10.1371/journal.pone.0123616
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Subdural Haematoma in Patients with Spontaneous Intracranial Hypotension

Abstract: Subdural haematoma (SDH) is a potentially life-threatening complication in patients with spontaneous intracranial hypotension (SIH). In serious cases, SIH patients who present with SDHs develop neurological deficits, a decreased level of consciousness, or cerebral herniation, and may even require an urgent neurosurgical drainage. Despite numerous publications on SDHs, few report its potential risk factors in patients with SIH. In this study, we retrospectively investigated 93 consecutive SIH patients and divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 40 publications
1
20
1
Order By: Relevance
“…SDH on MR imaging was rare in younger and female patients than in older and male patients . Females and younger patients had more severe headache and earlier presentation to the hospital.…”
Section: Discussionmentioning
confidence: 83%
“…SDH on MR imaging was rare in younger and female patients than in older and male patients . Females and younger patients had more severe headache and earlier presentation to the hospital.…”
Section: Discussionmentioning
confidence: 83%
“…Several studies reported possible complications of SIH, such as cerebral venous thrombosis, intracranial aneurysm, and subdural hematoma . Among these complications, the relationship between SDH and SIH has long been controversial .…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with the previous studies. Xia et al reported that the longer clinical course was the risk factor of SDH in SIH patients (OR, 1.06; 95% CI, 1.02‐1.1). Chung et al also reported that patients in the SIH group complicated by SDH experienced delayed diagnosis (11.7 vs. 31.3 days; P = .019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Axial and coronal non‐contrasted cerebral computed tomography images (Figure, A and B respectively) showed massive bi‐hemispheric acute (hyperdense) and chronic (hypodense) subdural haematoma, with extensive parenchymal compression. Dementia is strongly associated with brain atrophy and frequent falling, both of which are risk factors for subdural bleeding 1 caused by stretching and tearing of subdural veins 2 . The formation of a subdural haematoma can have further adverse effects in terms of cognitive decline.…”
mentioning
confidence: 99%